Dukungan Keluarga Terhadap Depresi Lansia: - Mulyani, Afrilia; Kusumaningsih, Meilia Rahmawati (Jurnal Skala Kesehatan, 2025)
In old age, various issues may arise, one of which is elderly depression. The prevalence of elderly depression in Central Java among individuals aged 55 to 64 years is 4.25%, those aged 65 to 74 years is 4.41%, and those aged over 75 years is 5.65% (Riskesdas, 2018). Family support is crucial for the elderly as they age. This literature review study aims to examine the relationship between family support and depression in the elderly. This study employs a literature review method using search databases such as Google Scholar and PubMed. The keywords used include “family support,” “family,” “depression,” “elderly depression,” and “elderly.” This study identified 11 articles for analysis. The analysis of several articles indicates that strong family support can help reduce depression in the elderly. Adequate support, including affection, attention, and sufficient facilities from the family, contributes to a sense of security and comfort, which ultimately improves the elderly’s mental well-being. The results of this literature review are expected to encourage family members to always provide support to the elderly.